Continuous spinal anaesthesia, an underutilised neuraxial technique in current anaesthesia practice: a timely reminder - Ong, E Theen; Ng, Hui Ping; Abd Ghani, Muhamad Rasydan; Wong, Shee Ven (Kugler Publications, 2022)
Continuous spinal anaesthesia (CSA) is a cardio-stable technique used in high-risk patients undergoing surgery. However, this technique appeared to decline over the last decades due concerns of complications that arise from using this technique, such as post-dural puncture headaches and neurological deficits. We report two cases of elderly patients, one at high cardiac risk and one with dementia and multiple comorbidities, under CSA for orthopaedic surgery with no reported complications. CSA is an adequeate anaesthetic technique with a low failure rate and complications. Proper technique should be taken into consideration to increase the success rate for this procedure.